RISK ASSESSMENT OF DAMAGE CAUSED BY LANDSLIDE IN THE MOUNTAINOUS DISTRICTS OF QUANG NGAI PROVINCE - Hung, Pham Van (Vietnam Journal of Earth Sciences, 2014)
This work presents the initial results of the risk assessment of damage caused by landslides in the mountainous districts of Quang Ngai province. Map damage risk in mountainous districts of Quang Ngai province was built on the basis of integrated maps with landslide risk map disaster resilience of socio-economic objects with spatial analysis in GIS environment. Most mountainous areas of Quang Ngai risk level low and very low losses, accounting for 65.64 % of the area , high and very high levels accounted for only 15.08 % of the natural area . Son Ha District at risk of damage caused by the landslides highest in the study area, followed by Tra Bong district . District Son Tay risk of damage to a minimum. These areas are at risk of damage caused by the landslides at high and very high concern when planning resource utilization territory, sustainable development of socio-economic and environmental protection: the Tra Phong, Tra Lanh and Tra Quan (Tay Tra district), Tra Son, Tra Thuy and Tra Lam (Tra Bong district), Son Tan, Son Mua (Son Tay district), Di Lang, Son Bao, Son Thanh, Son Thuong and Son Ha (Son Ha district); Long Hiep and Thanh An (Minh Long district), Ba Vi , Ba Vi and Ba To town (Ba To district). References Lê Mục Đích, 2001. Kinh nghiệm phòng tránh và kiểm soát tai biến địa chất”, Nxb. Xây Dựng, Hà Nội. (Dịch từ tiếng Trung Quốc). Phạm Văn Hùng, Nguyễn Văn Dũng, 2013. Cảnh báo nguy cơ trượt lở đất ở các huyện miền núi tỉnh Quảng Ngãi. Tạp chí Các Khoa học về Trái Đất, T.35, (2), tr.107-119. Guzzetti, F., A. Carrara, M. Cardinali, P. Reichenbach., 1999. “Landslide hazard evaluation: a review of current techniques and their application in a multi-scale study, Central Italy”, Geomorphology, vol. 31, no 1-4, p. 181-216. Saaty, Thomas L., 1994. Fundamentals of decision making and priority theory with analytic hierarchy process. Pittsburgh: RWS publications, 527p. Quy hoạch phát triển KT-XH tỉnh Quảng Ngãi đến năm 2020 (11/2010). UBND tỉnh Quảng Ngãi. Natural hazards Russia, V3, exogenous geological hazards, Crook, M, 2002. Natural hazards Russia, V3 Endogenous geological hazards, Crook, M, 2002. Natural hazards Russia, V6, Evaluation and management of natural risks, Crook, M, 2003.